Sources, transport, and deposition of metal(loid)s recorded by sulfide and rock geochemistry: constraints from a vertical profile through the epithermal Profitis Ilias Au prospect, Milos Island, Greece - Grosche, Anna; Klemd, Reiner; Denkel, Katja; Keith, Manuel; Haase, Karsten; Voudouris, Panagiotis C.; Alfieris, Dimitrios; Wiedenbeck, Michael (Mineralium Deposita, 2023)
Drill core samples from the Profitis Ilias Pb-Zn-Cu-Ag-Au vein mineralization on Milos Island, Greece provide new insights into (i) the metal sources, (ii) the primary vertical metal(loid) distribution, and (iii) the supergene enrichment processes in a transitional shallow-marine to subaerial hydrothermal environment. Metal contents of unaltered and altered host rocks combined with Pb isotope analyses of hydrothermal sulfides suggest that most metal(loid)s were derived by leaching of basement rocks, whereas the distinct enrichment of Te is related to the addition of Te by a magmatic fluid. The trace element contents of base metal sulfides record decreasing Au, Te, Se, and Co, but increasing Ag, Sb, and Tl concentrations with increasing elevation that can be related to progressive cooling and fluid boiling during the hypogene stage. The formation of base metal veins with porous pyrite hosting hessite inclusions at 400 m below the surface was triggered by vigorous fluid boiling. By contrast, the enrichment of native Au associated with oxidized Fe and Cu phases in the shallower part of the hydrothermal system resulted from supergene remobilization of trace Au by oxidizing meteoric water after tectonic exhumation to subaerial levels. Disseminated pyrite with higher Tl/Pb ratios and locally elevated Hg concentrations relative to vein pyrite reflects infiltration of the host rocks by boiled liquids and condensed vapor fluids. The vertical and temporal evolution of the Profitis Ilias mineralization, therefore, provides unique insights into the transport and precipitation of Au, Ag, Te, and related metal(loid)s by multiple fluid processes.
CRIS-Team Scopus Importer:2023-04-14
Keywords: Boiling; Epithermal deposits; Gold; Supergene enrichment; Tellurium